Additive manufacturing of photoactive polymers for visible light harvesting. (February 2019) - Zhakeyev, Adilet; Tobin, John; Wang, Huizhi; Vilela, Filipe; Xuan, Jin
Abstract: In recent years, 3D printing has gained a great deal of attention in the energy field, with numerous reports demonstrating its application in fabrication of electrochemical devices. The near-complete freedom of design offered by 3D printing technologies make them very appealing, since complex 3D parts can be directly fabricated. However, its application in photochemistry and solar energy harvesting remains, so far, an uncharted territory. In this work, a photoactive monomer was incorporated into commercially available 3D printing resin, which was subsequently used to successfully fabricate 3D photosensitizing structures for singlet oxygen generation. Results indicate that the SLA fabricated small-scale (0.1 ml) photoactive continuous flow reactor shows activity in singlet oxygen synthesis reaction under visible light irradiation (420 nm).